Development and technological research of medicated lozenges for catarrhal and aphthous stomatits` symptoms relief - Butkevych , Tetiana; Polova , Zhanna; Kuchmieieva, Oryna (The Ukrainian Scientific Medical Youth Journal, 2023)
inflammatory diseases of the oral cavity, in particular catarrhal and aphthous stomatitis, create significant discomfort for patients in everyday life. The occurrence of stomatitis in adolescents can be associated with numerous factors: bacterial and viral infection, insufficient oral hygiene, trauma of the mucous membrane, unbalanced nutrition, allergic reactions, some types of systemic diseases etc. Medicated lozenges have advantages for use in adolescents, as they have an interesting appearance (resembling a candy), pleasant taste and aroma, do not require swallowing or washing down with water, release active pharmaceutical ingredients by gradual dissolution in the oral cavity, which ensures their local action. The present work is aimed to develop different formulations of medicated lozenges for catarrhal and aphthous stomatits` symptoms relief. The objects of the study were experimental samples of lozenges with licorice root and propolis extracts. They were chosen as active ingredients due to their antimicrobial properties, as well as their ability to improve the general condition of the periodontium and reduce the outbreak of aphthae in stomatitis. Lozenges were prepared by heating and congealing method using different concentrations of active pharmaceutical ingredients and excipients (candy base substances – sugar substitute (isomalt), glucose syrup, carboxymethyl cellulose). 3 best formulations that had a uniform color distribution and were transparent, not sticky, had no external surface defects were subjects of the development and analysis. Obtained medicated lozenges were evaluated for physical parameters like weight variation, diameter and thickness, and pharmacotechnological evaluations like friability and hardness by pharmaceutical standard methods from State Pharmacopoeia of Ukraine 2.0 (2.9.5, 2.9.7, 2.9.8). Selected samples had homogeneous physical parameters: average weight in the range of 6.98-7.00 g (none of the formulations had a deviation of more than ± 5%), diameter 3.51 cm, thickness 5.04-5.11 mm. The obtained values of hardness and friability (less than 1% for all formulations) indicate satisfactory mechanical strength of the dosage form. Stability study was carried out at (15-25) ⁰С and 60±5 % humidity rate and was determined by evaluating the appearance and pharmacotechnological parameters. The values of hardness and friability were constant throughout the storage period for all formulations. Stability studies indicated that the formulations № 1 and 2 were stable for 30 days. The present research allowed to develop formulations for obtaining a pleasant-tasting dosage form intended for relatively slow dissolution in the oral cavity – medicated lozenges for use in adolescents to alleviate the symptoms of catarrhal and aphthous stomatitis.